Analisis uraian jabatan sebagai praktik implementasi manpower planning: Study pada perusahaan textile di Sukoharjo, Jawa Tengah - Rifqi Syarif Nasrulloh; Febriani Wahyusari Nurcahyanti; Fahmy Akbar Idries (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
This study aims to analyze the job description at TKSR company as a form of effort to implement workforce planning practices to create the company's organizational performance to run more effectively. This research uses participatory action research (PAR) techniques through a qualitative descriptive approach. The developed data collection method is a survey using questionnaires and interviews. The respondents in this survey were employees (staff and leaders) who cursed the unit of analysis selected as the sample. Data analysis techniques use descriptive qualitative. The results showed recommendations for the new organizational structure and a more detailed job description. The company must carry out a more responsive organizational restructuring in order to be able to place employees according to their positions appropriately, and this has an impact on the clarity of duties, authorities, and responsibilities of each employee. Organizations that carry out restructuring can adapt to the differences that arise in the organizational environment, and employees can play a significant role in improving the company's performance.